2013
DOI: 10.1123/jsep.35.4.419
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Mechanisms Underlying Doping Attitudes in Sport: Motivation and Moral Disengagement

Abstract: We examined whether constructs outlined in self-determination theory (Deci & Ryan, 2002), namely, autonomy-supportive and controlling motivational climates and autonomous and controlled motivation, were related to attitudes toward performance-enhancing drugs (PEDs) in sport and drug-taking susceptibility. We also investigated moral disengagement as a potential mediator. We surveyed a sample of 224 competitive athletes (59% female; M age = 20.3 years; M = 10.2 years of experience participating in their sport), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
99
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(123 citation statements)
references
References 51 publications
19
99
1
4
Order By: Relevance
“…First, controlled motivation was positively related to doping intentions through moral disengagement, while autonomous motivation was negatively linked to doping intentions through moral disengagement. These findings are consistent with previous studies [7,14,15] that have reported that contexts supporting controlled motivation are associated with attitudes about antisocial behaviors and drug-taking susceptibility or doping intentions through moral disengagement processes. More generally, this relationship is consistent with self-determination theory [25] and the findings of previous studies that have clearly established the maladaptive set of responses of controlled motivation in sport [42,43].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…First, controlled motivation was positively related to doping intentions through moral disengagement, while autonomous motivation was negatively linked to doping intentions through moral disengagement. These findings are consistent with previous studies [7,14,15] that have reported that contexts supporting controlled motivation are associated with attitudes about antisocial behaviors and drug-taking susceptibility or doping intentions through moral disengagement processes. More generally, this relationship is consistent with self-determination theory [25] and the findings of previous studies that have clearly established the maladaptive set of responses of controlled motivation in sport [42,43].…”
Section: Discussionsupporting
confidence: 93%
“…Studies that have examined doping variables from this theoretical point of view have shown indirect associations between self-determined motivation and doping. Hodge et al reported that contexts that support self-determination variables (autonomous vs. controlled motivation) are associated with attitudes about antisocial and prosocial behavior [14] and drug-taking susceptibility through moral disengagement processes [7]. These authors showed that autonomous motivation was negatively associated with the doping intentions, both directly and through moral disengagement.…”
Section: Self-determination Theory Self-regulatory Mechanisms and Domentioning
confidence: 99%
See 1 more Smart Citation
“…The number of studies dealing with this problem is still rather limited. Such factors as motivational orientation and motivational climate, sport motivation and moral disengagement [6,7,8] have been identified as possible predictors of such attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…When one lacks this nurturing, one is likely to substitute it by pursuing goals (e.g., gain ego enhancement, fame, and extrinsic rewards) that do not promote prosocial behavior (Gagné, 2003). In the few SDT-based studies that have examined moral functioning in sport, it has been shown that autonomously motivated athletes were more likely to report prosocial behaviors/attitudes Ntoumanis & Standage, 2009), and avoidance of antisocial behaviors such as using performance-enhancing drugs (Barkoukis, Lazuras, Tsorbatzoudis & Rodafinos, 2011); whereas controlled motivation was associated with antisocial behaviors/attitudes (Hodge, Hargreaves, Gerrard, & Lonsdale, 2013;Ntoumanis & Standage, 2009). Although the role of autonomous versus controlled motivation has been examined with respect to prosocial/antisocial behavior in sport, the role of basic psychological needs has not been examined relative to these moral variables.…”
Section: Basic Psychological Needs and Anti/prosocial Behaviormentioning
confidence: 99%